If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ((6 * 1) + (5x)) = 100 Multiply 6 * 1 ((6) + (5x)) = 100 (6 + (5x)) = 100 Remove parenthesis around (6 + (5x)) 6 + (5x) = 100 Solving 6 + (5x) = 100 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + (5x) = 100 + -6 Combine like terms: 6 + -6 = 0 0 + (5x) = 100 + -6 (5x) = 100 + -6 Combine like terms: 100 + -6 = 94 (5x) = 94 Divide each side by '5'. x = 18.8 Simplifying x = 18.8
| -6=3vn+6 | | -3m+9+7m=4m+19 | | -7x+2(7x+5)=66 | | 81+z=63 | | 9e-3=60 | | F(X)=x^3-5x^2-5x+25 | | -2k^2-k+12=3k^2+6k | | x+11+x=23 | | 4+3n=16.30 | | 11b+5-7= | | log(4)(4.5-3x)=log(4)4.5-log(4)3x | | 10x-6=4x-3(5+x) | | 18=3(3x-16) | | 17=-2+3x | | 0.7(3+9)=14.7 | | x+3+x=12 | | -21+x=x+11 | | -2x-3(3x+2)=-61 | | 10x+4-4x=-20 | | 6n-3+2=17 | | x+3+x+12=90 | | 3+2s=59 | | 3c-7c=0 | | 11-2u+34=33+u-33 | | -7x+5(-x-9)=39 | | 6(7x)=7(6x+13) | | 9x+.5y=51 | | -3x+2(-5x-7)=77 | | v-22+34=3v+11-33 | | 7+6x=-x-77 | | 3.14(15)= | | .5y=9x+51 |